CSIG-06. ELUCIDATING THE ROLE OF CO-OCCURRING MUTATIONS IN FGFR1-DRIVEN PEDIATRIC LOW-GRADE GLIOMA. (12th November 2021) - Morin, Eric; DiGiacomo, Jeromy; Malinowski, Seth; Alexandrescu, Sanda; Jones, David; Ligon, Keith; Bandopadhayay, Pratiti
Abstract: Pediatric low-grade gliomas (pLGGs) have excellent survival, however, with current standard of care, most patients suffer lifelong severe sequalae. pLGGs are almost exclusively driven by single activating mutations in the mitogen-activated protein kinase (MAPK) pathway. As targeted molecular therapy clinical trials focusing on BRAF -altered pLGGs are showing promising results in early clinical trials, similar efforts are underway for FGFR1 -altered tumors. In our cohort of FGFR1-4 altered gliomas, we observe frequent occurrence of a second alteration associated with activation of the MAPK or mammalian target of rapamycin (mTOR) pathways in pLGGs. Most commonly in the phosphatase N F1, PIK3CA, PIK3R1 PTPN11 or within the FGFR1 gene itself. However, the impact of second co-occurring mutations on therapeutic response and resistance has not been explored. To address this, we established mouse neural stem cell models over-expressing hot-spot mutated FGFR1 alone or in combination with a second alteration. Immunoblotting revealed that the addition of a second alteration attenuated phosphorylation of ERK, AKT and S6 and influenced cell proliferation both in normal growth conditions and in absence of growth factor. Treatment with an FGFR inhibitor (Infigratinib) showed reduced drug response in double mutant cells compared to hot-spot mutated FGFR1 alone. This was associated with less reduction of phosphorylation of ERK and S6 in the double mutant cells upon treatment. In conclusion, the presence of a second alteration influences proliferation and drug response in models of FGFR1 -mutated pLGG, potentially by modulating MAPK and mTOR signaling.